Recyclable nanocomposites of well-dispersed 2D layered silicates in cellulose nanofibril (CNF) matrix. (1st March 2022) - Li, Lengwan; Maddalena, Lorenza; Nishiyama, Yoshiharu; Carosio, Federico; Ogawa, Yu; Berglund, Lars A.
Abstract: Nanocomposites based on components from nature, which can be recycled are of great interest in new materials for sustainable development. The range of properties of nacre-inspired hybrids of 1D cellulose and 2D clay platelets are investigated in nanocomposites with improved nanoparticle dispersion in the starting hydrocolloid mixture. Films with a wide range of compositions are prepared by capillary force assisted physical assembly (vacuum-assisted filtration) of TEMPO-oxidized cellulose nanofibers (TOCN) reinforced by exfoliated nanoclays of three different aspect ratios: saponite, montmorillonite and mica. X-ray diffraction and transmission electron micrographs show almost monolayer dispersion of saponite and montmorillonite and high orientation parallel to the film surface. Films exhibit ultimate strength up to 573 MPa. Young's modulus exceeds 38 GPa even at high MTM contents (40–80 vol%). Optical transmittance, UV-shielding, thermal shielding and fire-retardant properties are measured, found to be very good and are sensitive to the 2D nanoplatelet dispersion. Graphical abstract: Unlabelled Image